The State Liability of Plastic Waste Dumping in Indonesia - Sonia, Vincentia; Sunyowati, Dina (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Plastic Waste has become one of the most important global environment issues these days. The study aims to scrutinize problems which are related to the phenomenon, such as: the principles and regulations of liability in regard of the plastic waste dumping, and also the restructuration and strengthening law and regulation to overcome the plastic waste dumping. The results found that since the states have liability on preventive environmental damages occurred within their territory, they must strengthen their international and national regulation in order to prevent any potential loss.